(untitled) (Comprehensive Journal of Science, 2026)
This study investigates the effectiveness of using short stories as an instructional strategy to enhance English vocabulary acquisition among EFL(English as a Foreign Language) learners in the College of Education in Libya. Vocabulary knowledge is foundational to language proficiency, yet many Libyan students struggle with retaining and using English vocabulary effectively. The study employed a mixed-methods design, combining quantitative data from pre- and post-vocabulary tests with qualitative insights from student interviews and teacher reflections. Participants included 60 first- year English major students, divided into control and experimental groups. The experimental group received vocabulary instruction through selected short stories, while the control group learned vocabulary via traditional methods (word lists and drills). Results showed that the experimental group demonstrated statistically significant improvement in vocabulary retention, usage accuracy, and learner motivation compared to the control group. Qualitative data also revealed that short stories increased students’ engagement, contextual understanding of words, and confidence in using new vocabulary. The study concludes that short stories are an effective, learner- centered tool for vocabulary development in Libyan higher education and recommends their integration into the English language curriculum.